Young Children's Probability of Dying Before and After Their Mother's Death: A Rural South African Population-Based Surveillance Study - Clark, Samuel J. (Public Library of Science, 2013)
BACKGROUND: There is evidence that a young child's risk of dying increases following the mother's death, but little is known about the risk when the mother becomes very ill prior to her death. We hypothesized that children would be more likely to die during the period several months before their mother's death, as well as for several months after her death. Therefore we investigated the relationship between young children's likelihood of dying and the timing of their mother's death and, in particular, the existence of a critical period of increased risk. METHODS AND FINDINGS: Data from a health and socio-demographic surveillance system in rural South Africa were collected on children 0–5 y of age from 1 January 1994 to 31 December 2008. Discrete time survival analysis was used to estimate children's probability of dying before and after their mother's death, accounting for moderators. 1,244 children (3% of sample) died from 1994 to 2008. The probability of child death began to rise 6–11 mo prior to the mother's death and increased markedly during the 2 mo immediately before the month of her death (odds ratio [OR] 7.1 [95% CI 3.9–12.7]), in the month of her death (OR 12.6 [6.2–25.3]), and during the 2 mo following her death (OR 7.0 [3.2–15.6]). This increase in the probability of dying was more pronounced for children whose mothers died of AIDS or tuberculosis compared to other causes of death, but the pattern remained for causes unrelated to AIDS/tuberculosis. Infants aged 0–6 mo at the time of their mother's death were nine times more likely to die than children aged 2–5 y. The limitations of the study included the lack of knowledge about precisely when a very ill mother will die, a lack of information about child nutrition and care, and the diagnosis of AIDS deaths by verbal autopsy rather than serostatus. CONCLUSIONS: Young children in lower income settings are more likely to die not only after their mother's death but also in the months before, when she is seriously ill. Interventions are urgently needed to support families both when the mother becomes very ill and after her death. Please see later in the article for the Editors' Summary